Basic logic for true and false LBVF (2007)
System LBVF is an extension of the classical positive logic, the system includes operators of alternating affirmation, alternating negation and determinability, and the operators of classical negation and good foundation are defined as from them. The system is characterized by a semantic of traditional valuations. Respect to the negation and affirmation operators the system is paracomplete.In the system the definitions of truth and falsity presented by Aristotle are really characterized, representing the Aristotelian falsity with the operator of alternating negation and the Aristotelian truth with the operator of alternating affirmation. This interpretation gives solution to a variant of the liar’s paradox.